Huge fetal sacrococcygeal teratoma with a completely formed eye and intratumoral DNA ploidy heterogeneity - Sergi, Consolato M.; Ehemann, Volker; Beedgen, Bernd; Linderkamp, Otwin; Otto, Herwart F. (Pediatric and developmental pathology, 1999)
Preterm infants and newborns with sacrococcygeal teratomas are at high risk for prenatal and perinatal complications. The prognosis depends on size and histology of the tumor, degree of prematurity, associated malformations, route of delivery, and prompt and complete surgical removal. Virtually any tissue can be present in a sacrococcygeal teratoma, but to date, ocular lens has been documented only as lentinoids (lens-like cells), whereas flow-cytometric data have been variably interpreted. We describe a case of a sacrococcygeal teratoma in an infant of 29 weeks gestational age that is remarkable for the weight (4500 g), the presence of a completely formed eye, and intratumoral DNA ploidy heterogeneity.
Gesehen am 08.11.2017